Wireless communications and networks - Stallings, William; Stallings, William (Upper Saddle River, NJ : Pearson/Prentice Hall, 2005)
A comprehensive overview of wireless communication systems that covers transmission fundamentals, protocols and TCP/IP suite, antennas, signal encoding techniques, spread spectrum, coding and error control, satellites, mobile IPs, Wi-Fi, and other related topics.
Rev. ed. of: Wireless communications and networking. Pearson Prentice Hall, c2002.
Includes bibliographical references (p. 540-546) and index.
Adult.
Adult
Keywords: Wireless communication systems; Wireless LANs; Local area networks; Wireless communication systems